2022
DOI: 10.3389/fenvs.2022.896524
|View full text |Cite
|
Sign up to set email alerts
|

China Carbon Neutralization Research Status and Research Frontier Tracking

Abstract: In the context of global joint response to climate change, carbon neutralization has become one of the main measures for governments, enterprises, and even individuals around the world to deal with global warming. This article explores the current research status and frontier trends in the field of carbon neutralization, which can not only provide theoretical reference for the follow-up research of carbon neutralization but also provide useful ideas for the policy-making of carbon neutralization. The study is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Keyword burst describes the significant change in the frequency of a keyword over a period of time, reflecting the research hotspots and emerging trends (Shi et al, 2022). With the help of CiteSpace's burst feature, this study presents the top four keywords with the strongest citation burst in TOD research, as shown in Figure 8.…”
Section: Abstract Burst Analysismentioning
confidence: 95%
“…Keyword burst describes the significant change in the frequency of a keyword over a period of time, reflecting the research hotspots and emerging trends (Shi et al, 2022). With the help of CiteSpace's burst feature, this study presents the top four keywords with the strongest citation burst in TOD research, as shown in Figure 8.…”
Section: Abstract Burst Analysismentioning
confidence: 95%
“…The CiteSpace version 6.1.R2 on 64-bit was used for the analysis. CiteSpace is among one of the popular software to analyze scientometric based results (Noor et al, 2021;Feng et al, 2022;Shi et al, 2022). It also shows various types of interactive visualization (i.e., network analysis and visualization), such as most active areas, major related areas, key papers for a given area, critical transitions in the history of the development of the field and its turning points.…”
Section: Software Toolmentioning
confidence: 99%
“…Agriculture is an important part of the economy, so the development of agriculture also depends on technological progress [ 3 ]. Under the background of “carbon peak and carbon neutralization”, it is not enough to rely only on the progress of traditional agricultural technology, but also pay more attention to the development of agricultural low-carbon technology [ 4 ]. With a large population, scattered agricultural resources, and scarce agricultural resources per capital, China must adopt new agricultural technologies to break the constraints of agricultural production resources in order to achieve sustainable agricultural development [ 5 ].…”
Section: Introductionmentioning
confidence: 99%